Macroeconomic Developments and Convergence Report for 2000 - West African Monetary Institute (Accra, Ghana: WAMI, 2000)
The Report assesses the level of macroeconomic convergence attained by the member states of the West African Monetary Zone during 2000. The report shows the level of compliance with the primary macroeconomic convergence criteria by the member states and articulated policy actions for ensuring that all member countries satisfy the stipulated convergence criteria by 2002.
Its also written in French language.
rpm 30/10/13
Loans
Keywords: Macroeconomics; Macroeconomics developments